2022
DOI: 10.1186/s12967-022-03249-2
|View full text |Cite|
|
Sign up to set email alerts
|

Demethylation at enhancer upregulates MCM2 and NUP37 expression predicting poor survival in hepatocellular carcinoma patients

Abstract: Background Identification of novel biomarker is important for development of molecular-targeted therapy agents for patients with hepatocellular carcinoma (HCC). This study aims to identify potential prognostic biomarkers and investigate epigenetic mechanism of HCC development. Methods Public bulk-RNA seq datasets and proteomic dataset were screened for identification of potential prognostic biomarkers for HCC patients. Public methylomic datasets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 31 publications
(26 reference statements)
0
32
1
Order By: Relevance
“…Accumulating evidence suggests that epigenetic dysregulation modulates liver cancer development by regulating tumor-associated gene expression [ 20 23 ]. Unlike promoter/enhancer demethylation-mediated upregulation of ITPR3, MCM2 and NUP37 in hepatocellular carcinoma [ 20 , 21 ]. In this study, we first revealed that DNA methylation degree of COL12A1 promoter/enhancer was not demethylated in iCCA relative to the adjacent nontumor samples, indicating that COL12A1 upregulation is independent of the methylation level of its promoter/enhancer region in clinical iCCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that epigenetic dysregulation modulates liver cancer development by regulating tumor-associated gene expression [ 20 23 ]. Unlike promoter/enhancer demethylation-mediated upregulation of ITPR3, MCM2 and NUP37 in hepatocellular carcinoma [ 20 , 21 ]. In this study, we first revealed that DNA methylation degree of COL12A1 promoter/enhancer was not demethylated in iCCA relative to the adjacent nontumor samples, indicating that COL12A1 upregulation is independent of the methylation level of its promoter/enhancer region in clinical iCCA.…”
Section: Discussionmentioning
confidence: 99%
“…Re-analyses of DNA methylation datasets GSE156299 [ 35 ] and TCGA-CHOL [ 6 ] were performed to decipher the methylation patterns of COL12A1 gene in iCCA and nontumor liver tissues. The raw data of DNA methylation were processed using minifi (version 1.38.0) as previously described [ 21 , 36 ]. Weighted gene co-expression network analysis (WGCNA) was performed for weighted correlation network analysis of gene expression patterns in iCCA [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the above-mentioned histone chaperones, the roles of other histones in digestive cancers are being researched. MCM2, a well-recognized proliferation marker and histone chaperone, is highly expressed in HCC, EC, GC, and CRC, and negatively correlates with their prognosis [ 155 , 156 , 157 , 158 ]. Interestingly, less is known about the regulatory network mechanism of MCM2 in digestive cancer.…”
Section: Histone Chaperones In Digestive Cancersmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], we have been notified that the Figure 2 was published incorrectly. Also, the Figures 2 and 7 captions should be extended and Funding note needs to be corrected.…”
Section: Correction: Journal Of Translational Medicine (2022) 20:49 ...mentioning
confidence: 99%